Identification of the factors that influence the performance of extension management systems in Kweneng and Southern districts of Botswana - Terblanche, S.E. (Stephanus Esaias), 1940- (University of Pretoria, 2018)
Dissertation (MSc (Agric))--University of Pretoria, 2018.